Editorial - Gomes, Suely; Braga, Claudomilson Fernandes; Martins, Dalton Lopes; Signates, Luiz (Comunicação & Informação, 2016)
Editorial Revista 2016-1 – v.19 nº 1. Comunicação e Informação ISSN versão impressa: 1415-5842 ISSN versão eletrônica: 2317-675X